The Profile of Students’ Physics Problem Solving Ability in Optical Instruments - Awal Mulia Rejeki Tumanggor; Jumadi Jumadi; Insih Wilujeng; Ernila Siringo Ringo (Program Studi Pendidikan Fisika Universitas Negeri Jakarta, LPPM Universitas Negeri Jakarta, HFI Jakarta, HFI, 2019)
This research aims to analyze the profile of students’ problem-solving ability in problems of optical instruments. This survey research involved 65 students class XI of MAN 3 Yogyakarta. The research instrument was in the form of 3 problem-solving questions in the form of a description. The results showed the percentage of students in the expert category was still relatively low at 30,7% and the students in the novice category were quite high at 69,3% so that students’ overall physics problem-solving abilities were relatively low. In this research, some student difficulties were still found, one of which was in determining the focus of the right lens for patients with eye disorders to use glasses and determine magnification when using a magnifying glass. Efforts to implement innovative learning are needed to improve problem-solving abilities in overcoming students’ physics problems.